2016
DOI: 10.1016/j.yjmcc.2016.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells suppress cardiac alternans by activation of PI3K mediated nitroso-redox pathway

Abstract: Background The paracrine action of non-cardiac progenitor cells is robust, but not well understood. Mesenchymal stem cells (MSC) have been shown to enhance calcium (Ca++) cycling in myocytes. Therefore, we hypothesized that MSCs can suppress cardiac alternans, an important arrhythmia substrate, by paracrine action on Ca++ cycling. Methods and Results Human cardiac myocyte monolayers derived from iPS cells (hCM) were cultured without or with human MSCs (hMSC) directly or plated on a transwell insert. Ca++ tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…53 Sattayaprasert et al further showed that hMSC conditioned media reduces calcium transient alternans and shortens calcium transient duration in hydrogen peroxide treated human induced pluripotent stem cell derived-cardiac myocyte monolayers. 55 Similarly, mouse MSC conditioned media attenuated the occurrence of arrhythmic calcium transients of ischemia/reperfusion injured isolated ventricular myocytes. 56 Thus, across species, hMSC conditioned media appears to have favorable effects on calcium handling in cultured cardiomyocytes.…”
Section: Stem Cell Secretomes Can Impact Cardiomyocyte Eccmentioning
confidence: 98%
See 2 more Smart Citations
“…53 Sattayaprasert et al further showed that hMSC conditioned media reduces calcium transient alternans and shortens calcium transient duration in hydrogen peroxide treated human induced pluripotent stem cell derived-cardiac myocyte monolayers. 55 Similarly, mouse MSC conditioned media attenuated the occurrence of arrhythmic calcium transients of ischemia/reperfusion injured isolated ventricular myocytes. 56 Thus, across species, hMSC conditioned media appears to have favorable effects on calcium handling in cultured cardiomyocytes.…”
Section: Stem Cell Secretomes Can Impact Cardiomyocyte Eccmentioning
confidence: 98%
“…51 On the other hand, in hydrogen peroxide treated human induced pluripotent stem cell derived-cardiac myocyte monolayers, hMSC conditioned media significantly decreased action potential alternans relative to control. 55…”
Section: Stem Cell Secretomes Can Impact Cardiomyocyte Eccmentioning
confidence: 99%
See 1 more Smart Citation
“…Co-culturing cells, namely on a Transwell insert within a companion plate, is a well-established model to investigate cell-cell interactions in vitro (Sattayaprasert et al, 2016, Heiss et al, 2015. As described in the methods section, two co-culture approaches were used in this study.…”
Section: Hl-1 Cell-endothelial Cell Co-culture Systemmentioning
confidence: 99%
“…Numerous studies have shown the regenerative potential of MSCs to counteract organ failures (Xing et al, 2014 ; Desando et al, 2016 ; Sattayaprasert et al, 2016 ). It has also been demonstrated that injecting MSC conditioned medium and not the cells themselves can induce the same effects.…”
Section: Introductionmentioning
confidence: 99%